Quantum Differentiation and Index Theorems - Schulz-Baldes, Hermann; Stoiber, Tom (Springer, 2022)
As already stressed in the overview in Preface, this chapter is the mathematical core of this book. In the next Sect. 3.1 the Hankel and Toeplitz operators associated to a W∗ -dynamical system are introduced and then the traceclass Peller criterion is proved. Combining an L2 -criterion with interpolation theory, Sect. 3.2 then proves Peller criteria for higher Schatten classes.
CRIS-Team Scopus Importer:2024-12-16